2015
DOI: 10.1016/j.ssnmr.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR studies of proteins immobilized on inorganic surfaces

Abstract: Solid state NMR is the primary tool for studying the quantitative, site-specific structure, orientation, and dynamics of biomineralization proteins under biologically relevant conditions. Two calcium phosphate proteins, statherin (43 amino acids) and leucine rich amelogenin protein (LRAP; 59 amino acids), have been studied in depth and have different dynamic properties and 2D- and 3D-structural features. These differences make it difficult to extract design principles used in nature for building materials with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) has been utilized for structural investigations on bones and teeth, including studies of proteins (29)(30)(31)(32)(33)(34)(35)(36). Time-of-flight secondary ion mass spectroscopy (ToF-SIMS) has proven to be a useful method for the chemical analyses of HAP in enamel and bone tissue, as well as for analyses of organic molecules, such as protein fragments (33,(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
mentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) has been utilized for structural investigations on bones and teeth, including studies of proteins (29)(30)(31)(32)(33)(34)(35)(36). Time-of-flight secondary ion mass spectroscopy (ToF-SIMS) has proven to be a useful method for the chemical analyses of HAP in enamel and bone tissue, as well as for analyses of organic molecules, such as protein fragments (33,(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
mentioning
confidence: 99%
“…[17,18] Methods of solid-state NMR have opened the door to challenging but high resolution structural biology studies[19] of amelogenin in a mineral-bound state. Shaw and colleagues have recently demonstrated that mouse amelogenin undergoes a random coil to beta-sheet transition upon mineral binding,[20] that surface-induced structural changes occur for both phosphorylated and non-phosphorylated forms of LRAP,[21] and that molecular level interactions may change with phosphorylation state leading to macroscopic differences in adsorption or mineralization.…”
mentioning
confidence: 99%
“…At globally undersaturated (that is, 1 mM) silicic acid concentrations, P 5 S 3 slowed down the dissolution of silica . Here, we report on the conformation of the peptide in the presence or absence of silica as derived from NMR and CD 19, spectroscopy. We show that the P 5 S 3 polypeptide backbone is disordered in solution but shifts to a higher α‐helical content upon binding silica.…”
Section: Introductionmentioning
confidence: 93%
“…In a solid state NMR approach, significant perturbations in the chemical shifts of both the peptide backbone and side‐chain C and N atoms were reported. These were attributed to differences in the chemical environments due to interaction with silica (that is, peptide‐silica interaction, peptide‐chain assembly), and no information about peptide folding was inferred . In another report, R5 was studied by solution state NMR in the presence of 50 μM (undersaturated) silicic acid.…”
Section: Introductionmentioning
confidence: 99%